Manajemen Peningkatan Kinerja Guru : (Studi Kasus di Yayasan Pondok Pesantren Sulthon Rinjani Sekolah Menengah Pertama Islam Terpadu) - rusandi, haeruman; Mukhlisin Asyrafuddin, Nurul; Makky, Khalid; halimatuzzahrah, halimatuzzahrah; Helmiyatun, Helmiyatun (Indonesian Journal of Teaching and Learning, 2023)
This study aims to determine the planning of teacher performance improvement, organizing teacher performance improvement, implementing teacher performance improvement and evaluating teacher performance improvement. The method used in this study is qualitative research with a phenomenological approach and the techniques used are observation, interviews and documentation. Research subjects of the Principal, vice-principal and teacher. Data analysis techniques use data reduction, data presentation and conclusions. Guarantor of the validity of the researcher's data using trust, transferability, dependability and assertiveness The results of the research obtained in this study are: (1) Planning for improving teacher performance at the Sulthon Rinjani NW Dasan Poto IT Junior High School Foundation has been carried out with meetings / meetings between the principal, teachers and other school personnel so that appropriate planning can be determined in teacher performance. (2) Organizing teacher performance improvement in SMP IT Foundation Sulthon Rinjani NW Dasan Poto is still lacking, because there are still teachers at the high school / MA education level for the junior high school level and there are still groups of teachers who teach who are not in accordance with their expertise with those taught. (3) The implementation of teacher performance at the Sulthon Rinjani NW Dasan Poto IT Junior High School Foundation is still not carried out because the school's facilities and support for the teaching and learning process are still lacking. (4) Evaluation of teacher performance improvement at SMP IT Sulthon Rinjani NW Dasan Poto Foundation is carried out by providing direction / guidance and improvements in teacher performance